Melaminium iodide monohydrate - Zhao, Min Min (International Union of Crystallography, 2010)
In the title melaminium salt, 2,4,6-triamino-1,3,5-triazin-1-ium iodide monohydrate, C(3)H(7)N(6) (+)·I(−)·H(2)O, the components are linked via N—H⋯O, N—H⋯N, O—H⋯I and N—H⋯I hydrogen bonds. All of the H atoms of the melaminium cation are involved in hydrogen bonds. The melaminium cations are interconnected by four N—H⋯N hydrogen bonds, forming ribbons along [111]. The water molecules connected by N—H⋯O hydrogen bonds also form part of these ribbons. The ribbons are interconnected by other hydrogen bonds (O—H⋯I and N—H⋯I), as well as by π–π interactions [centroid–centroid distance = 3.6597 (17) Å].